ANALISIS PENERAPAN PP 46 TAHUN 2013 ATAS PAJAK PENGHASILAN WAJIB PAJAK ORANG PRIBADI USAHAWAN DIBIDANG USAHA JASA PADA TOKO TONNY - Poluan, Dayna M.; Sondakh, Jullie J.; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
In 2013 the Government implemented the Income Tax Regulation, namely PP No. 46 of 2013 with a calculation scheme of 1% multiplied by turnover or gross profit and gross circulation of less than 4.8 billion per year. This study aims to determine the application of PP No. 46 of 2013 at Tonny Stores in accordance with the existing tax laws. This study uses descriptive analysis methods and data obtained through interviews and documentation. This study will also compare PP 46 of 2013 with the Calculation of Net Income Norms and the latest tax rules PP 23 of 2018. The results of this study indicate PP 46 of 2013 reduces the amount of tax paid compared to Net Income Calculation Norms and also makes it easy to calculate the amount Personal Income Tax is payable so that it can minimize errors in determining the amount of income tax that must be paid by the company. Keywords: Income tax, Norma Calculations, PP 46 in 2013